“Estimación del índice de mérito total del programa de mejoramiento genético en bovinos de leche de la parroquia Guaytacama del cantón Latacunga, provincia de Cotopaxi” - Gualan Puchaicela, Lilia Esperanza (2023)
Producers in the Guaytacama parish spend most of their time raising cattle, most of which belong to the Holstein breed, considered one of the largest milk producers. The lack of records and the inadequate technical management of the cattle has resulted in a high cost of milk production per liter, which leads to economic unsustainability in their production. This led us to determine the estimation of the total merit index of the sustainable genetic improvement program for dairy cattle. This study was carried out in the Guaytacama parish of the Latacunga canton, Cotopaxi province, their objectives were to estimate the economic value of the characteristics of the improvement objective, calculate the genetic value of each animal, and analyze the response to selection. Information was collected for the months (April, May, June 2023), having as characters to evaluate production costs those that covered feeding, health and other expenses generated in the productive systems, which were collected through a survey, for the analysis of estimated breading value, characters as weight gain, liters produced and milk density were taken, 23 herds were considered, which in their totality constituted 97 specimens to be studied (calves, cows, adult cows, bulls and bulllets). For the tabulation of production costs, cost-benefit formulas were applied using the Excel program and for the other characteristics the BLUP method was used. In conclusion, the cost of production of a liter of milk in monthly average is $ 0.15 knowing that the average expense generated in the whole parish is $52.09 destined to feed, the cost of sale received by the intermediary is $0.42 for each liter of milk produced, which represents a monthly profit of $81.85 that does not even adjust to the fourth part of the basic salary making this production inefficient. As for the estimated breading value (EVB breeding value), with a reliability of 4 %, it yielded average values for daily weight gain of 355.82gr; density 0.27g/ml and liters of milk 2.54 g/ml, which is considered within the acceptable range, while different variations were obtained due to the management system both in feeding and health of these individuals. For the response to the selection, 4 individuals (Querida, Estrella, Juana, Suca) were obtained that meet standards both in density, liters of milk and weight gain, so they should be used for reproduction of the next generations since they showed favorable values.